Analisis Kepuasan Anggota Koperasi Serba Usaha Madani Kotabaru Dengan Metode IPA (Importance Performance Analysis) - Rosida Rosida; Hairudinor Hairudinor; Taharuddin Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2018)
The objectives of this study are (1) to determine member satisfaction of ‘Madani’ Business Multipurpose Cooperation, Kotabaru based on the level of need and level of performance in the dimensions of direct evidence (tangible), reliability, responsiveness, assurance and empathy, (2) to determine which attributes belong to the main priority and maintained, or the excessive low priority, (3)  to determine the width of the gap or gap between the importance and the performance of services.This type of this research was descriptive quantitative. In this study the author compared the level of need with the level of performance in producing satisfaction. Data were collected using questionnaires, and the samples of 121 cooperative members were selected by accidental sampling. Data analysis used IPA (Importance Performance Analysis) and gap analysis.The analysis result of the suitability level of the lowest attributes of the service quality was responsiveness (responsiveness) with the attribute of quick responsiveness in responding to complaints/ problems (87.71%), and the highest dimension was direct evidence (tangible) in the attributes of cleanliness and tidiness of office and employees (101.10%).The analysis of Importance Performance Analysis (IPA) showed that there were four more dominant attibutes in quadrant B (Preserve Achievement) at IPA Cartesian diagram, as follows:1.     Completeness, preparedness and cleanliness of equipments of ‘Madani’ Business Multipurpose Cooperation, Kotabaru (3)2.     Knowledge and skills of tellers and customer service officers (9)3.     Politeness and trustworthiness owned by the employees of  the office of ‘Madani‘ Business Multipurpose Cooperative, Kotabaru (10)4.     Responsibility for the comfort of its members (12)The highest value gap  was in the dimension of responsiveness with the value of -0.55. Meanwhile,  the lowest gap was the dimension of assurance with the value of -0.02. For the value gap (gap), the highest gap was quick response attribute in facing complaints/problems (7) with the value of -0.55, and the lowest gap was the attributes of cleanliness and tidiness of the office and employees (1) with the value of 0.05, and the service was fast, accurate, friendly and ready to help (6) with the value of 0.05. Keywords: Cooperation member satisfaction, level of interest, level of performance